2017
DOI: 10.1371/journal.pgen.1006828
|View full text |Cite
|
Sign up to set email alerts
|

p63 exerts spatio-temporal control of palatal epithelial cell fate to prevent cleft palate

Abstract: Cleft palate is a common congenital disorder that affects up to 1 in 2500 live births and results in considerable morbidity to affected individuals and their families. The aetiology of cleft palate is complex with both genetic and environmental factors implicated. Mutations in the transcription factor p63 are one of the major individual causes of cleft palate; however, the gene regulatory networks in which p63 functions remain only partially characterized. Our findings demonstrate that p63 functions as an esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 58 publications
(91 reference statements)
5
66
0
Order By: Relevance
“…Examination of cluster e9 revealed that it was equivalent to the periderm based on its expression of known marker genes, including Grhl3, Arhgap29, Sfn and Irf6 (Auden et al, 2006; de la Garza et al, 2013; Hammond et al, 2017;Kousa et al, 2017;Paul et al, 2017;Richardson et al, 2017Richardson et al, , 2014. Cells within this cluster had a very discrete set of marker genes compared with all other ectodermal clusters (Table 1, Fig.…”
Section: Periderm Cells With Altered Morphology Initially Occur At Thmentioning
confidence: 96%
“…Examination of cluster e9 revealed that it was equivalent to the periderm based on its expression of known marker genes, including Grhl3, Arhgap29, Sfn and Irf6 (Auden et al, 2006; de la Garza et al, 2013; Hammond et al, 2017;Kousa et al, 2017;Paul et al, 2017;Richardson et al, 2017Richardson et al, , 2014. Cells within this cluster had a very discrete set of marker genes compared with all other ectodermal clusters (Table 1, Fig.…”
Section: Periderm Cells With Altered Morphology Initially Occur At Thmentioning
confidence: 96%
“…Last, a recent ChIP-Seq analysis of P63 binding in E13.5/E14.5 (pooled) WT mouse palatal shelves reported as primary targets the following GRN candidates ( Figure 1A): Cldn3, Col171a, Fermt1, Ifitm3, Irf6, Krt7/8, Osr2, Pltp, and Trim29, but not Cbln1 or Krt15 in this particular upper jaw tissue. 26 2.2 | p63 network candidate genes have homologs in mammals, fish, frog, and bird Data compiled from NCBI's HomoloGene supported our hypothesis that members of the proposed tooth-specific, jawindependent GRN are deeply conserved among vertebrates ( Figure 3). Of the 32 candidate genes flagged by our lab, 18 17 genes had homologs reported in four model organisms, Mus musculus, Xenopus tropicalis, D. rerio, and Gallus gallus, for four major vertebrate groups, Mammalia, Amphibia, Actinopterygii (within the class Osteichthyes), and Aves, respectively ( Figure 3).…”
Section: Support For a Putative P63-regulated Grn For Mouse Teethmentioning
confidence: 57%
“…Each of these four major signaling pathways was previously linked to odontogenesis and p63 , supporting that they participate in a p63 ‐driven GRN. Last, a recent ChIP‐Seq analysis of P63 binding in E13.5/E14.5 (pooled) WT mouse palatal shelves reported as primary targets the following GRN candidates (Figure A): Cldn3, Col171a, Fermt1, Ifitm3, Irf6, Krt7/8, Osr2, Pltp, and Trim29, but not Cbln1 or Krt15 in this particular upper jaw tissue …”
Section: Resultsmentioning
confidence: 86%
“…Chromatin configuration data indicate it binds to the ZNF750 promoter in keratinocytes 50 . The mouse ortholog of ZNF750 (i.e., ZFP750) is expressed in murine oral epithelium 51 , and oral periderm 43 , and the zebrafish ortholog To determine whether the shared binding sites reflect sequence homology between ppl-10 and PPL-8.3, we performed sequence alignments. We found that a 467 bp core sequence from the zebrafish enhancer (plus-strand) is marginally more identical to a 400 bp core sequence from the human enhancer (plus-strand) relative to several control sequences including: the zebrafish minus-strand (reverse-complement), the non-biological reverse sequence, and non-biological sequences of similar lengths produced by Fisher-Yates shuffling of the plus-strand sequence (see Material & Methods, File 2b).…”
Section: Zebrafish Periderm Enhancers Share a Binding Site Code With mentioning
confidence: 99%